Thoracoscopic pericardial window surgery for complex postoperative pericardial effusion after cardiac surgery: A case series - Gia, Nguyen Duy; Huy, Nguyen Quang; Thang, Nguyen Duy; Hung, Le Van; Tuyen, Trinh Thi Thanh; Anh, Trieu The; Tu, Vu Ngoc (Tạp chí Nghiên cứu Y học, 2026)
Postoperative pericardial effusion is a common complication after cardiac surgery, particularly when the effusion is recurrent, or clinically significant. When the effusion is predominantly posterior, or associated with clot formation, percutaneous drainage begins difficult or ineffective. We retrospectively reviewed 6 patients who developed clinically significant pericardial effusion after open cardiac surgery and underwent left thoracoscopic posterior pericardial window. Imaging showed non-drainable loculated or posterior effusions in all cases. The interval from surgery to effusion ranged from 10 days to 2 months. Intraoperative findings included clotted hemopericardium, hemorrhagic effusion, and serous effusion. Histopathology showed chronic pericarditis without malignancy or tuberculosis. All patients improved after surgery, with no recurrence, mortality, or major complication at 3 months.